2013
DOI: 10.12732/ijpam.v84i5.1
|View full text |Cite
|
Sign up to set email alerts
|

A New One Parameter Family of Iterative Methods With Eighth-Order of Convergence for Solving Nonlinear Equations

Abstract: In this paper, a new one parameter family of iterative methods with eighth-order of convergence for solving nonlinear equations is presented and analyzed. This new family of iterative methods is obtained by composing an iterative method proposed by Chun [3] with Newton's method and approximating the first-appeared derivative in the last step by a combination of already evaluated function values. The proposed family is optimal since its efficiency index is 8 1/4 ≈ 1.6818. The convergence analysis of the new fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The approach in this paper establishes the local convergence result under hypotheses only on the first derivative and give a larger convergence ball than the earlier studies, under weaker hypotheses. Notice that in earlier studies [19,23] the convergence is shown under hypotheses on the eighth derivative. The same technique can be used to other methods.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…The approach in this paper establishes the local convergence result under hypotheses only on the first derivative and give a larger convergence ball than the earlier studies, under weaker hypotheses. Notice that in earlier studies [19,23] the convergence is shown under hypotheses on the eighth derivative. The same technique can be used to other methods.…”
Section: Introductionmentioning
confidence: 91%
“…where F : D ⊆ S → T is a Fréchet-differentiable operator defined on a convex set D, where S, T are subsets of R or C. Equation of the form (1.1) is used to study problems in Computational Sciences and other disciplines [3,7,14,16,20]. Newton-like iterative methods [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23] are famous for approximating a solution of the equation (1.1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…J. Yun [10] proposed a three-step iterative method, which is a significant improvement of the method proposed by Noor and Noor [8]. Siyyam [9] derived and analyzed a new fourth-step iterative method with fifth order of convergence. Al-Subaihi and Alqarni [3] developed optimal three-step methods with eighth order of convergence.…”
Section: Introductionmentioning
confidence: 99%